2011
DOI: 10.1051/0004-6361/201015843
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the solar irradiance during the Holocene

Abstract: Context. Long-term records of solar radiative output are vital for understanding solar variability and past climate change. Measurements of solar irradiance are available for only the last three decades, which calls for reconstructions of this quantity over longer time scales using suitable models. Aims. We present a physically consistent reconstruction of the total solar irradiance for the Holocene. Methods. We extend the SATIRE (Spectral And Total Irradiance REconstruction) models to estimate the evolution o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
284
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(299 citation statements)
references
References 77 publications
7
284
2
6
Order By: Relevance
“…On decadal to centennial timescales, SATIRE reproduces observations such as the composite of the Lyman-α line at 121.6 nm (since 1947, Woods et al, 2000), the measured solar photospheric magnetic flux (since 1967), the empirically reconstructed solar open magnetic flux (since 1845, Lockwood et al, 2014), and the 44 Ti activity in stony meteorites (Krivova et al, 2010;Vieira et al, 2011;Yeo et al, 2014). SATIRE and NRLSSI2 are internally consistent, in the sense that the integral of the modeled spectral irradiances equals the TSI.…”
Section: Satirementioning
confidence: 56%
“…On decadal to centennial timescales, SATIRE reproduces observations such as the composite of the Lyman-α line at 121.6 nm (since 1947, Woods et al, 2000), the measured solar photospheric magnetic flux (since 1967), the empirically reconstructed solar open magnetic flux (since 1845, Lockwood et al, 2014), and the 44 Ti activity in stony meteorites (Krivova et al, 2010;Vieira et al, 2011;Yeo et al, 2014). SATIRE and NRLSSI2 are internally consistent, in the sense that the integral of the modeled spectral irradiances equals the TSI.…”
Section: Satirementioning
confidence: 56%
“…These follow the protocol of the Paleoclimate Modeling Intercomparison Project, Phase 3 (PMIP3) (Schmidt et al 2011;Braconnot et al 2012). Prescribed external forcing factors are: variations in volcanic aerosols (Crowley and Unterman 2012), in total solar irradiance (TSI) (Vieira et al 2011) and in the atmospheric concentration of the most important well-mixed greenhouse gases and anthropogenic aerosols (Schmidt et al 2011); changes in global land-cover and agricultural areas (Pongratz et al 2008); and annual values of the orbital parameters, that is, eccentricity, obliquity, and perihelion. In addition, we use an 1156-year-long control simulation under constant preindustrial (1850) boundary conditions (hereafter PiControl) as a reference for the forced experiments.…”
Section: Model Description and Experimental Setupmentioning
confidence: 99%
“…Horizontal solid lines are the discrete levels extracted following the algorithm described in Little et al (2011). b Annual globally averaged values of the reconstructed TSI (black line, in W/m 2 ) (Vieira et al 2011) and the simulated volcanic forcing, shown as net adiative flux anomalies, long plus short waves (LW + SW, in W/m 2 ), at the top of the atmosphere with respect to the climatological mean. The volcanic forcing is for Past1000-R3.…”
Section: North Atlantic Climate Regimes Before and After The Shiftmentioning
confidence: 99%
“…This unavoidable fact is at the heart of all reconstructions, even those that build in intermediate physical models (e.g. Wang et al 2005;Vieira et al 2011). Noting that "a proxy for the long-term activity of the quiet Sun does not yet exist", S2011 hypothesized that centennial time-scale QS brightness changes vary linearly with large-scale variations associated with the heliospheric solar magnetic field.…”
Section: The Reconstructions Of S2011mentioning
confidence: 99%